A Study of the Incidence of an Increment Value Land Tax - Plehn, Carl C. (Quarterly Journal of Economics, 1918)
I. General considerations, 487. — Taxation conditions in Europe and the United States, 489. — II. Analysis of the effects of an increment tax of the British type, 490. — III. Numerical illustrations of the results of this type of increment tax, 497. — IV. Comparison with the results of the general property tax in the United States, 504.